Suture and venous traction test analysis in dogs fixed in alcohol and preserved in saline solutions - Pelogia, Marina E. S. [UNESP]; Cerqueira, Eduardo S. F. [UNESP]; Silveira, Camila P. B. [UNESP]; Rolim, Glauco S. [UNESP]; Fechis, Alisson D. S. [UNESP]; Rocha, Thiago A. S. S. [UNESP]; Laus, Jose L. [UNESP]; Oliveira, Fabricio S. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2018)
The objective of this research was to determine in necropsied dogs the best time for fixation in ethylic alcohol (EA) and preservation in 30% sodium chloride aqueous solution (SCAS 30 0 /0), aiming micro-surgical training. Five groups of necropsied dogs (G1 to G5) were fixed with EA, and put in boxes containing EA for 30 (G2), 60 (G3), 90 (G4) or 120 days (G5). After that, each group was preserved in SCAS 30% for 120 days. The control group (G1) was composed by cadavers without fixation/preservation. At the end of each period, two fragments of external jugular vein per cadaver were collected, for traction test. Immediately after the collection, the cadavers femoral veins were evaluated (by 2 people) regarding the suture quality in binocular surgical microscope, and attributed scores from 0 (bad) to 5 (excellent), regarding the fresh samples. The average at the maximum rupture strength of the G3 fixation end (21.51N), such as the average of the G2 preserving end (21.62N) remained closer to the control group (19.98N) and the G2 was the group with the best score for venous suture training. The EA was efficient as a fixative just like SCAS as a dog cadavers' preservative. The small change of the traction test values, together with the best suture score, indicated the group kept for 30 days in EA and SCAS (G2) as the best for venous micro-surgical training.
Keywords: Suture; venous traction test; dogs; saline solution; canine; conservation; preservation; surgery; training